2021
DOI: 10.3389/fonc.2021.781162
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Immune Checkpoint Blockades in the Treatment of Ocular Melanoma: A Systematic Review and Meta-Analysis

Abstract: AimThis meta-analysis aimed to compare the efficacy and safety of immune checkpoint blockade for the treatment of ocular melanoma.MethodsWe searched the PubMed, EMBASE, and Cochrane Library databases up to July 2021. Effect sizes (ESs) and corresponding 95% confidence intervals (CIs) were used to compare the outcomes. Efficacy outcomes included complete response (CR), partial response (PR), stable disease (SD), progressive disease (PD), objective response rate (ORR), overall survival (OS), progression free sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Immune checkpoint inhibitors can suppress the tumor immune microenvironment by reducing the immune cells [26,27]. Among them, anti-programmed death-1 (PD-1) and anti-CTLA-4 have already been used to treat patients with metastatic UVM in the clinic [28,29], and a meta-analysis showed that immune checkpoint blockade immunotherapy was helpful in improving the OS of UVM patients [30]. Recent studies have shown that m6A RNA modification plays an essential role in both physiological and pathological conditions, especially in the initiation and progression of different types of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitors can suppress the tumor immune microenvironment by reducing the immune cells [26,27]. Among them, anti-programmed death-1 (PD-1) and anti-CTLA-4 have already been used to treat patients with metastatic UVM in the clinic [28,29], and a meta-analysis showed that immune checkpoint blockade immunotherapy was helpful in improving the OS of UVM patients [30]. Recent studies have shown that m6A RNA modification plays an essential role in both physiological and pathological conditions, especially in the initiation and progression of different types of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Anti CTLA-4 drugs, such as tremelimumab and ipilimumab, were also used in patients with metastatic UM. A previous meta-analysis showed that immune checkpoint blockade immunotherapy was helpful for the treatment of UM patients in terms of long-term survival ( 62 ). In this study, the PD-1 expression was increased in the high-risk group.…”
Section: Discussionmentioning
confidence: 99%